2008
DOI: 10.1182/blood.v112.11.2098.2098
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab and Rituximab Combination Therapy for Patients with Untreated CLL – a Phase II Trial.

Abstract: Despite the availability of multiple therapeutic regimens, without a stem cell transplant, chronic lymphocytic leukemia (CLL) remains an incurable disease. A dramatic response rate with intensive chemo-immunotherapy in patients with CLL is frequently associated with irreversible long term consequences to the bone marrow, limiting further therapeutic options. For this reason we have initiated a clinical trial combining Rituximab (RIT) and Alemtuzumab (ALEM), two monoclonal antibodies with established activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Frankfurt et al reported on 20 previously untreated and symptomatic patients with CLL who received alemtuzumab with rituximab administered sc. 14 The median age of the group was 54 years. Approximately 75% achieved a CR, including all 5 patients with an 11qabnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Frankfurt et al reported on 20 previously untreated and symptomatic patients with CLL who received alemtuzumab with rituximab administered sc. 14 The median age of the group was 54 years. Approximately 75% achieved a CR, including all 5 patients with an 11qabnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Frankfurt et al reported the results of subcutaneous alemtuzumab administration in 20 previously untreated and symptomatic patients. 109 A high CR rate was achieved (40%), including all patients with del11q abnormality. Furthermore at the completion of therapy 70% of patients had no evidence of MRD by flow-cytometry.…”
Section: Rituximab In Combination With Monoclonal Antibodiesmentioning
confidence: 90%
“… 32 Combining alemtuzumab with R has been explored in the relapsed/refractory 33 , 34 setting with some activity that led to further development of this regimen in the upfront approaches. 35 , 36 It is important, however, to note that we have learned that not all patients are appropriate for alemtuzumab treatment as it is less effective in patients with bulky nodal disease (>5 cm). 30 In fact, Tam et al reviewed the outcome of 99 patients who were F-refractory and ineligible or refractory to alemtuzumab.…”
Section: Treatment Of Relapsed and Refractory Diseasementioning
confidence: 99%